PENGEMBANGAN PRODUK EKONOMI KREATIF BERBASIS BUDAYA LOKAL UNTUK MENINGKATKAN DAYA SAING UMKM DI DESA TANJUNG BENOA - Putu Ratna Windusara Putri; Fahmi Tanjung; I Made Wisnu Wardana; I Made Sujana (Yayasan Nusantara Hasana Berdikari, 2024)
The creative economy has become one of the strategic sectors contributing significantly to local economic development and community welfare. Tanjung Benoa Village possesses rich cultural assets and tourism potential that can be transformed into creative economy products with high economic value. However, many Micro, Small, and Medium Enterprises (MSMEs) in the area still face challenges in product innovation, branding, marketing, and integrating local cultural values into commercial products. This community service program aimed to strengthen the capacity of MSME actors through the development of creative economy products based on local culture. The methods employed included socialization, training, product development workshops, mentoring, and evaluation. A total of 40 MSME actors participated in the program. The results demonstrated significant improvements in participants’ understanding of product innovation, cultural branding, packaging design, and digital marketing strategies. Participants successfully developed products that reflected local cultural identity while increasing market attractiveness and competitiveness. The program contributed to enhancing the sustainability and competitiveness of MSMEs in the tourism area of Tanjung Benoa.